The Possibility of Using Oil Pomace as a Substitute for Walnuts (Juglans regia L.) in Muesli Bar Technology - Patryk Siczek; Justyna Libera (Foods)
The utilization of food industry waste to create innovative, high-quality products with reduced environmental impact is a growing trend in food technology. Walnut oil pomace, a byproduct of walnut oil production, is rich in nutrients and bioactive compounds, making it an excellent candidate for reuse in muesli bars as a replacement for walnuts. The aim of the study was to evaluate the possibility of replacing walnuts with oil pomace in muesli bar recipes and to assess whether the resulting product meets quality standards. Ground expeller walnut oil pomaces and aqueous extract were tested, with a bar containing ground walnuts serving as the reference sample. The bars were evaluated for sensory, physicochemical, and antioxidant properties, and their nutritional values were assessed. Results showed that the pomace-enriched bars exhibited satisfactory physicochemical properties, with texture, color, and safety (as measured by water activity and pH) comparable to the control bars. Sensory evaluations classified all bars as acceptable, with no significant differences in nutritional value. The study concludes that walnut pomace holds promise as a sustainable ingredient in food technology, potentially expanding product diversity while reducing environmental impact. This concept aligns with promoting sustainable practices in food manufacturing.